2007
DOI: 10.4049/jimmunol.179.9.6318
|View full text |Cite
|
Sign up to set email alerts
|

Hsp72 Induces Inflammation and Regulates Cytokine Production in Airway Epithelium through a TLR4- and NF-κB-Dependent Mechanism

Abstract: Heat shock proteins are generally regarded as intracellular proteins acting as molecular chaperones; however, Hsp72 is also detected in the extracellular compartment. Hsp72 has been identified in the bronchoalveolar lavage fluid (BALF) of patients with acute lung injury. To address whether Hsp72 directly activated airway epithelium, human bronchial epithelial cells (16HBE14o-) were treated with recombinant Hsp72. Hsp72 induced a dose-dependent increase in IL-8 expression, which was inhibited by the NF-κB inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 51 publications
8
95
0
Order By: Relevance
“…25 This response was blocked by treatment with either anti-Hsp70 antibody or anti-IL-6 antibody demonstrating that TLR-2 dependent IL-6/Stat3 pathway is involved. Besides being a chaperone, the cytokine properties of Hsp70 are also well documented in studies showing its interaction with TLR4/CD14 complexes 18,23,26 or to TLR2. 23,27 Similarly, studies by Multhoff's group showed that tumor cells that express higher Hsp70 on their surface are killed significantly better by natural-killer (NK) cells compared to tumor cells that express low Hsp70 levels.…”
Section: Exosomal Membrane Molecules and Immune Response Activationmentioning
confidence: 94%
See 2 more Smart Citations
“…25 This response was blocked by treatment with either anti-Hsp70 antibody or anti-IL-6 antibody demonstrating that TLR-2 dependent IL-6/Stat3 pathway is involved. Besides being a chaperone, the cytokine properties of Hsp70 are also well documented in studies showing its interaction with TLR4/CD14 complexes 18,23,26 or to TLR2. 23,27 Similarly, studies by Multhoff's group showed that tumor cells that express higher Hsp70 on their surface are killed significantly better by natural-killer (NK) cells compared to tumor cells that express low Hsp70 levels.…”
Section: Exosomal Membrane Molecules and Immune Response Activationmentioning
confidence: 94%
“…Previous studies have demonstrated that rHsp70 can bind to different TLRs on the cell surface leading to activation of NF-kB and MAP kinase pathways. [17][18][19] Stimulation of TLRs, in general, leads to increased pro-inflammatory response including phagocytosis.20,21 Therefore, it is possible that exosomal Hsp70 interacts with TLRs on the cell surface thereby initiating signaling pathways, such as NF-kB (proposed model depicted in Fig. 2), that ultimately leads to increased phagocytosis and phago-lysosome fusion.…”
Section: Exosomal Membrane Molecules and Immune Response Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies indicate that HSPs are recognized mainly by TLR-4. 37,38 Activation of immune cells by HSPs (and possibly by other DAMPs) via TLR-4 may raise concerns about endotoxin contamination masking the observed immunostimulatory effects. In our model, neutrophil attraction induced by apoptotic cells was independent of TLR-4, which excludes the involvement of HSP60, HSP70 and HSP72.…”
Section: N=10 N=12 N=9mentioning
confidence: 99%
“…Primers used for hsc70 genotyping and RT-PCR were H1 (3Ј-tggcttagacaaaaaggttgg), and H2 (3Ј-cttggggatacgggttgag) and control ␤-actin primers were Act1 (3Ј-atggatgacgatatcgctgc) and Act2 (3Ј-ctagaagcacttgcggtgcac). Peptide gp [33][34][35][36][37][38][39][40][41] …”
Section: Chemicals and Reagentsmentioning
confidence: 99%